Benzodithiophene‐Based Broad Absorbing Random Copolymers Incorporating Weak and Strong Electron Accepting Imide and Lactam Functionalized Pyrrolo[3, 4‐c]pyrrole Derivatives for Polymer Solar Cells. Issue 9 (16th March 2015) - Tamilavan, Vellaiappillai; Roh, Kyung Hwan; Agneeswari, Rajalingam; Lee, Dal Yong; Cho, Shinuk; Jin, Youngeup; Park, Sung Heum; Hyun, Myung Ho
<x xml:space="preserve">Abstract</x> Two benzodithiophene (BDT)‐based broad absorbing low band gap random copolymers, P1 and P2, incorporating electron accepting imide functionalized pyrrolo[3, 4‐c]pyrrole‐1, 3‐dione (TDPPDT) and lactam functionalized pyrrolo[3, 4‐c]pyrrole‐1, 4‐dione (DKPP) derivatives are prepared. The copolymerization of differently alkylated two TDPPDT derivatives with both of BDT and DKPP offers random copolymers P1 and P2. The absorption bands of polymers P1 and P2 cover the region from 300 to 900 nm and the estimated band gaps of P1 and P2 are 1.43 and 1.39 eV, respectively. The highest occupied molecular orbital energy levels of P1 and P2 are identical, at –5.25 eV. The organic field effect transistors made from P1 and P2 provide a hole mobility μ of 3.0 × 10−4 and 3.6 × 10−5 cm2 V−1 s−1, respectively. Polymer solar cells (PSCs) prepared from P1 and P2 afford a maximum power conversion efficiency of 1.64% and 2.14%, respectively.